Coding paediatric outpatient data to provide health planners with information on children with chronic conditions and disabilities. (7th October 2016) - Craig, Elizabeth; Kerr, Neal; McDonald, Gabrielle
Abstract : Aim: In New Zealand, there is a paucity of information on children with chronic conditions and disabilities (CCD). One reason is that many are managed in hospital outpatients where diagnostic coding of health‐care events does not occur. This study explores the feasibility of coding paediatric outpatient data to provide health planners with information on children with CCD. Methods: Thirty‐seven clinicians from six District Health Boards (DHBs) trialled coding over 12 weeks. In five DHBs, the International Classification of Diseases and Related Health Problems, 10th Edition, Australian Modification (ICD‐10‐AM) and Systematised Nomenclature of Medicine Clinical Terms (SNOMED‐CT) were trialled for 6 weeks each. In one DHB, ICD‐10‐AM was trialled for 12 weeks. A random sample (30%) of ICD‐10‐AM coded events were also coded by clinical coders. A mix of paper and electronic methods were used. Results: In total 2, 604 outpatient events were coded in ICD‐10‐AM and 693 in SNOMED‐CT. Dual coding occurred for 770 (29.6%) ICD‐10‐AM events. Overall, 34% of ICD‐10‐AM and 40% of SNOMED‐CT events were for developmental and behavioural disorders. Chronic medical conditions were also common. Clinicians were concerned about the workload impacts, particularly for paper‐based methods. Coder's were concerned about clinician's adherence to coding guidelines and the poor quality of documentation in some notes. Conclusion: Coded outpatient data could provide planners with a rich source of information on children with CCD. However, coding is also resource intensive. Thus its costs need to be weighed against the costs of managing a much larger health budget using very limited information.